2010
DOI: 10.14710/jitaa.35.2.101-108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Genotype on Response in Body Composition to Variation in Dietary Protein : Energy Ratios

Abstract: An experiment with 480 day-old chicks of four commercial strains was conducted to study the effect of genotype on response in body composition to variation in dietary protein: energy ratios. The chicks were randomly allocated into 4x2x4 factorial and fed on a commercial starter diet (250 g CP and 12.5 MJ of ME /kg) from hatching to 5 d of age and divided into two groups with three replications each of 16 birds and given either the such starter diet (S) or a finisher diet (F) containing 190 g CP and 13.0 MJ of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…However, FCR for both sexes was not significant (P>0.05). This indicates that males required a higher level of dietary lysine than females for maximal BWG and dietary digestible lysine for FCR was higher than for BWG (Greenwood et al, 2005;Dozier et al, 2009;Dozier et al, 2010;Indarsih and Pym, 2010;Mehri et al, 2010). Male growing chickens gained faster than females due to higher daily feed intake in males (Samadi and Libiert, 2006) were also observed in this study.…”
Section: Performancesupporting
confidence: 71%
See 1 more Smart Citation
“…However, FCR for both sexes was not significant (P>0.05). This indicates that males required a higher level of dietary lysine than females for maximal BWG and dietary digestible lysine for FCR was higher than for BWG (Greenwood et al, 2005;Dozier et al, 2009;Dozier et al, 2010;Indarsih and Pym, 2010;Mehri et al, 2010). Male growing chickens gained faster than females due to higher daily feed intake in males (Samadi and Libiert, 2006) were also observed in this study.…”
Section: Performancesupporting
confidence: 71%
“…Therefore, some studies revealed the need to correct the proportion levels of crude protein to lysine (Harm and Russell, l995;Labadan et al, 2001). This is due to the fact that the lysine requirement is higher than the NRC (1994) requirement measured with the experimental situation (Lehmann et al, 1996;Kerr et al, 1999;Rezaei et al, 2004;Aftab et al, 2007;Indarsih and Pym, 2010). Breast meat deposition can be optimized on feeding at a higher level of lysine in the starter and finisher diets than those recommended by NRC (1994) as studied by Rezaei et al (2004).…”
Section: Introductionmentioning
confidence: 99%